Interruptions and transitions : essays on the senses in medieval and early modern visual culture - Baert, Barbara (Art and material culture in medieval and renaissance Europe,, 2019)
Interruptions and Transitions: Essays on the Senses in Medieval and Early Modern Visual Culture is an anthology of the most recent works by Barbara Baert, discussing the connection between the experiences of the senses in the medieval and early modern visual culture, the hermeneutics of imagery, and the limits and possibilities of contemporary Art Sciences. The six chapters include Pentecost, Noli me tangere , the woman with an issue of blood, the Johannesschüssel , the dancing Salome, and the role of the wind. The reader is shown a medieval and early modern visual culture as a history of artistic solutions, as the fascinating approach between biblical texts, plastic imagination, and the art-scientific métier. This makes him a privileged guest in a unique in-between space where humans and their artistic expression can meet existentially.